Concept Analysis: "Cultural Disruption" in Indigenous Cardiac Patients and Its Implications for Nursing Practice - Wahyuni, Aria; Oktorina, Rola; Yenni, Yenni (REAL in Nursing Journal, 2025)
Background: Indigenous populations experience disproportionately high rates of cardiovascular disease (CVD), yet their encounters with healthcare systems often involve cultural disconnection and marginalization. Despite increasing use of terms such as cultural safety and competence, the specific phenomenon of cultural disruption—particularly in hospital-based cardiac care—remains underexplored and poorly defined in nursing literature.Purpose: This concept analysis aims to explore and clarify the meaning of cultural disruption as it relates to Indigenous patients undergoing cardiovascular care, with a focus on implications for nursing practice.Methods: Walker and Avant’s eight-step method of concept analysis was employed to identify the defining attributes, antecedents, consequences, and empirical referents of cultural disruption. Data were synthesized from peer-reviewed articles published within the last 10 years, including qualitative studies and Indigenous health frameworks relevant to cardiac care.Results: Cultural disruption is characterized by disconnection from cultural identity and practices, invalidation of Indigenous knowledge systems, breakdown in relational and community support, spiritual alienation, and erosion of trust in healthcare systems. Antecedents include colonization, systemic racism, and biomedical dominance, while consequences include treatment non-adherence, patient disengagement, and poor health outcomes. Empirical referents include patient-reported cultural safety assessments, narrative interviews, and clinical documentation audits.Conclusion: Cultural disruption is a distinct and critical concept in understanding health inequities experienced by Indigenous cardiac patients. Recognizing this phenomenon enables nurses to implement culturally responsive strategies that uphold spiritual, relational, and community-based dimensions of care. Future research is needed to validate tools that assess cultural disruption and evaluate outcomes of culturally grounded interventions in cardiovascular nursing.